Efficacy and safety of a reduced dose of plerixafor in combination with granulocyte colony‐stimulating factor in healthy haploidentical stem cell donors. Issue 6 (24th March 2022) - Kurnikova, Elena; Trakhtman, Pavel; Balashov, Dmitry; Garloeva, Juliya; Kumukova, Irina; Khismatullina, Rimma; Pershin, Dmitriy; Shelikhova, Larisa; Novichkova, Galina; Maschan, Alexey
Abstract: Background and Objectives: Implementation of the technique of immunomagnetic selection requires the procurement of a large number of CD34+ cells from haploidentical donors within a single apheresis procedure. The release of stem cells with granulocyte colony‐stimulating factor (G‐CSF) alone is unsatisfactory in a number of donors, and plerixafor, a CXCR4 chemokine receptor antagonist, could be used as an additional mobilization agent. The aim of our study was to examine whether a lower dose of plerixafor (0.12 mg/kg) can provide sufficient increase in CD34+ cells in the peripheral blood of allogeneic healthy donors in comparison with a historical control group. In addition, we assessed the risk of inability to provide the recipient with a transplant containing the optimal dose of 8–10 × 10 6 CD34+ cells/kg body weight of the recipient. Materials and Methods: In a prospective, single‐arm study, we examined the results of 105 mobilizations in healthy adult haploidentical donors with G‐CSF and plerixafor at a dose of 0.12 mg/kg. The historical control group consisted of 106 mobilizations with G‐CSF and plerixafor at 0.24 mg/kg. Results: The median increase in the number of CD34+ cells from day 4 to day 5 of mobilization was 69 cells/μl (range, 28–240) versus 77 cells/μl (24–217) in the groups of 0.12 and 0.24 mg/kg of plerixafor, respectively ( p ‐value 0.255). The apheresis products contained a median of 14.4 × 10 6 /kg recipient body weight CD34+ cells versus 12.9 × 10 6 /kg in the groups that received 0.12 and 0.24 mg/kg of plerixafor, respectively ( p ‐value 0.118). The obtained differences were not significant, which means the application of a decreased dose of plerixafor did not affect the results of mobilization. Conclusion: The obtained differences in collection were not significant, and thus the application of a decreased dose of plerixafor did not affect the results of mobilization.